PERLUASAN MODEL PENERIMAAN TEKNOLOGI MENGGUNAKAN VARIABEL MINDFULNESS: STUDI KASUS ADOPSI E-WALLET DI KOTA BENGKULU - Purbondaru, Sekar Ayu (UNIB Press, 2025)
The use of cashless payment systems continues to increase in line with developments in technology, information and digital communications. This study examines the main determinants of e-wallet use intention and proposes a model of e-wallet adoption, integrating mindfulness as a significant factor. The respondents in this study are e-wallet users living in Bengkulu City aged 17-40 years old. The non-probability sampling technique was used to obtain data samples from respondents. Online survey questionnaires collected respondents of this study through social media such as WhatsApp and Instagram. After adopting the listwise deletion method through Mahalanobis Distance on SEM-AMOS, 257 useable questionnaires were available for analysis. For data analysis, Confirmatory Factor Analysis (CFA), assessment of normality, and regression weights were applied to this research. The result indicates that (1) mindfulness has a positive and significant effect on perceived usefulness; (2) mindfulness has a positive and significant effect on perceived ease to use; (3) perceived usefulness has a positive and significant effect on the intention to use; (4) perceived ease to use has no significant effect on the intention to use; and (5) intention to use has a positive and significant effect on actual use. Keywords: E-wallet, Mindfulness, Perceived Usefulness, Perceived Ease to use, Intention to Use, Actual Use, TAM